Gambaran Konsep Diri Anak Berhadapan Dengan Hukum di Sentra Wirajaya di Makassar - Ananda, Rizka Ayu; Zainuddin, Kurniati; Sulastri, Tri (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Self-concept is an important thing that will determine how a person views himself. It is important for every child to have a good self-concept so that undesirable things do not happen, such as committing crimes that will bring them into trouble with the law. This research aims to determine the description of children's self-concept in dealing with the law, the factors that influence children's self-concept in dealing with the law. This research uses a qualitative case study research method where data collection used is in the form of interview and documentation techniques. The respondents in this study were two children in conflict with the law. The research results showed that both respondents, through the aspects of self-knowledge, self-assessment and self-expectation, found that the self-concept of Children in Conflict with the Law was positive. The respondent's self-knowledge is very good, he is able to accept his own strengths and weaknesses. Respondents' self-assessment was very positive, they really respected themselves and others. As well as positive self-hope for the future. However, family relationships are a factor that influences the self-concept of Children in Conflict with the Law and other factors, namely peer and community factors. On the other hand, if there is not a good relationship, the child tends to have a negative self-concept towards himself.